Prevalência de sobrepeso e obesidade e fatores associados em universitários da área da saúde no centro-oeste brasileiro - Faria Filho, Humberto Carlos de (Universidade do Vale do Rio dos Sinos, 2020)
Objectives: To verify the prevalence and the factors associated with overweight and obesity in university students in the health area in central-western Brazil. Methods: This is a cross-sectional, university-based study, with a sample of 2,245 university students, of both sexes, from health courses at a university located in the state of Goiás. The presence of overweight and obesity were defined by the Body Mass Index (BMI) entre 25.0 and 29.9 kg/m2 and ≥ 30 kg/m2, respectively. Associated factors included sociodemographic and behavioral characteristics, family history and the presence of comorbidities. For data analysis, Poisson regression was used and stratified by sex. Results: The mean age of the sample was 22.7 years (standard deviation ± 4.1) and comprised 69.5% women. The general prevalence of overweight and obesity was 20.2% (95% CI: 18.5 - 21.8) and 6.2% (95% CI: 5.2 - 7.2), respectively, which are significantly higher among men (34.5%; 95% CI: 30.9 - 38.1 and 11.3%; 95% CI: 8.9 - 13.6, respectively), when compared to women (13.9%; 95% CI : 12.2 - 15.6 and 4%; 95% CI: 3.0 - 4.9, respectively). After adjustment, there was a statistically significant association between age, smoking, family history and the presence of comorbidities with the occurrence of overweight and obesity in both sexes. Among women, a significantly higher probability for the occurrence of overweight and obesity was identified among academics aged 24 years or older and among those with smoking habits. As well, the occurrence of overweight and obesity was higher among students with an obese mother and father and among those with two or more comorbidities. Among men, similar findings were found, but with lesser magnitudes of associations. Conclusion: There was a high prevalence of overweight and obesity among academics in the health field, with sociodemographic and family history factors being more associated with their occurrence than behavioral factors.
Keywords: Sobrepeso; Obesidade; Prevalência; Fatores associados; Universitários; Overweight; Obesity; Prevalence; Associated factors; College students; ACCNPQ::Ciências da Saúde::Saúde Coletiva